Formaldehyde and acetaldehyde emissions from residential wood combustion in Portugal - Cerqueira, Mário; Gomes, Luís; Tarelho, Luís; Pio, Casimiro (Atmospheric Environment, 2013)
A series of experiments were conducted to characterize formaldehyde and acetaldehyde emissions from residential combustion of common wood species growing in Portugal. Five types of wood were investigated: maritime pine (Pinus pinaster), eucalyptus (Eucalyptus globulus), cork oak (Quercus suber), holm oak (Quercus rotundifolia) and pyrenean oak (Quercus pyrenaica). Laboratory experiments were performed with a typical wood stove used for domestic heating in Portugal and operating under realistic home conditions. Aldehydes were sampled from diluted combustion flue gas using silica cartridges coated with 2,4-dinitrophenylhydrazine and analyzed by high performance liquid chromatography with diode array detection. The average formaldehyde to acetaldehyde concentration ratio (molar basis) in the stove flue gas was in the range of 2.1–2.9. Among the tested wood types, pyrenean oak produced the highest emissions for both formaldehyde and acetaldehyde: 1772 ± 649 and 1110 ± 454 mg kg−1 biomass burned (dry basis), respectively. By contrast, maritime pine produced the lowest emissions: 653 ± 151 and 371 ± 162 mg kg−1 biomass (dry basis) burned, respectively. Aldehydes were sampled separately during distinct periods of the holm oak wood combustion cycles. Significant variations in the flue gas concentrations were found, with higher values measured during the devolatilization stage than in the flaming and smoldering stages.
Keywords: Acetaldehyde; Biomass combustion; Emissions; Formaldehyde; Wood stove

Inventory of fine particulate organic compound emissions from residential wood combustion in Portugal - Gonçalves, Cátia; Alves, Célia; Pio, Casimiro (Atmospheric Environment, 2012)
In the early fall of 2010 a survey questionnaire was conducted to assess residential wood combustion (RWC) practices in the 18 districts of mainland Portugal. This paper describes and analyses the results from a bottom-up approach, based on this telephone survey, which enabled the characterisation of RWC practices in each district. Additionally, emission factors and source proﬁles obtained from different RWC tests, allowed the estimation of CO, CO2, PM2.5 and particulate organic compound emissions on a country-scale. The type and number of RWC appliances, each with their speciﬁc emissions factor and the amount and type of fuel used vary signiﬁcantly on a district scale. The energy consumption in RWC appliances was estimated to be 35 342 TJ y 1 . The estimated emissions of PM2.5 from RWC in Portugal (10.96 kt y 1 ) represent 30% of the estimate for different source activities reported in a recent inventory. The national emissions of OC and EC were estimated to be 5.32 and 0.53 kt y 1 , respectively. It was also estimated that the total CO2 emissions from RWC in Portugal are 1.7 Mt y 1 . The levoglucosan emissions contribute with between 7.8% and 16.1% of PM2.5 emissions from RWC
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Burning appliances; Emission factors; Inventory; survey questionnaire; Wood species

Fireplace and woodstove fine particle emissions from combustion of western Mediterranean wood types - Alves, Célia; Gonçalves, Cátia; Fernandes, Ana Patrícia; Tarelho, Luís; Pio, Casimiro (Atmospheric Research, 2011)
Wood from seven species of trees grown in the Portuguese forest (Pinus pinaster, Eucalyptus globulus, Quercus suber, Acacia longifolia, Quercus faginea, Olea europea and Quercus ilex rotundifolia), and briquettes produced from forest biomass waste were burned in a ﬁreplace and in a woodstove to determine the chemical composition of ﬁne particle (PM2.5) emissions. Samples were analysed for organic and elemental carbon (OC/EC), water soluble ions (Na+ , NH4 + , K+ , Mg 2+ , Ca 2+ , Cl− , NO3 − and SO4 2− ) and 67 elements. The PM2.5 emission factors (g kg−1 fuel burned, dry basis) were in the ranges 9.9–20.2 and 4.2–16.3, respectively, for the ﬁreplace and the woodstove. Organic carbon contributed to about 50% of the ﬁne particle mass in the emissions from every wood species studied in both burning appliances. The carbonaceous component of PM2.5 was dominated by organic carbon, accounting for more than 85% of the total carbon (TC): OC/TC ranged from 0.85 to 0.96 (avg. 0.92) for the ﬁreplace and from 0.86 to 0.97 (avg. 0.93) for the woodstove. The water-soluble ions accounted for 0.64 to 11.3% of the PM2.5 mass emitted from the ﬁreplace, whereas mass fractions between 0.53 and 13.6% were obtained for the woodstove. The golden wattle wood smoke showed a much higher ionic content than the emissions from the other wood types. Trace elements represented 0.4 to 2.5% and 0.2 to 2.2% of the PM2.5 mass emitted, respectively, from the ﬁreplace and the woodstove, which corresponded to average total emissions of 132± 77.3 mg kg−1 and 93.4± 60.8 mg kg−1 of wood burned. Among these, K, Pb, Al, Mn and Sr were present in all samples. From the emission proﬁles of the individual experiments, composite wood combustion proﬁles are suggested with the aid of a cluster analysis.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Biomass burning; Fireplace; metals; OC/EC; PM2.5; Water-soluble ions; Woodstove

Characterisation of PM10 emissions from woodstove combustion of common woods grown in Portugal - Gonçalves, Cátia; Alves, Célia; Evtyugina, Margarita; Mirante, Fátima; Pio, Casimiro; Caseiro, Alexandre; Schmidl, Christoph; Bauer, Heidi; Carvalho, Fernando (Atmospheric Environment, 2010)
A series of source tests was performed to evaluate the chemical composition of particle emissions from the woodstove combustion of four prevalent Portuguese species of woods: Pinus pinaster (maritime pine), Eucalyptus globulus (eucalyptus), Quercus suber (cork oak) and Acacia longifolia (golden wattle). Analyses included water-soluble ions, metals, radionuclides, organic and elemental carbon (OC and EC), humic-like substances (HULIS), cellulose and approximately l80 organic compounds. Particle (PM10) emission factors from eucalyptus and oak were higher than those from pine and acacia. The carbonaceous matter represented 44e63% of the particulate mass emitted during the combustion process, regardless of species burned. The major organic components of smoke particles, for all the wood species studied, with the exception of the golden wattle (0.07e1.9% w/w), were anhydrosugars (0.2e17% w/w). Conﬂicting with what was expected, only small amounts of cellulose were found in wood smoke. As for HULIS, average particle mass concentrations ranged from 1.5% to 3.0%. The golden wattle wood smoke presented much higher concentrations of ions and metal species than the emissions from the other wood types. The results of the analysis of radionuclides revealed that the 226 Ra was the naturally occurring radionuclide more enriched in PM10. The chromatographically resolved organics included n-alkanes, nalkenes, PAH, oxygenated PAH, n-alkanals, ketones, n-alkanols, terpenoids, triterpenoids, phenolic compounds, phytosterols, alcohols, n-alkanoic acids, n-di-acids, unsaturated acids and alkyl ester acids.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd
Keywords: Biomass burning; Emissions; GC-MS; Organic tracers; PM10; Woodstove